2020
DOI: 10.1021/acs.jnatprod.9b00607
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Biosynthesis of Pyranocoumarins: Isolation and 13C-Incorporation Analysis by High-Performance Liquid Chromatography–Ultraviolet–Solid-Phase Extraction–Nuclear Magnetic Resonance Data

Abstract: Citrus sinensis and Citrus limonia were obtained by germination from seeds, and isotopic-labeling experiments using d-[1-13C]­glucose were performed with the seedlings. After 60 days, the seedlings were analyzed by high-performance liquid chromatography–ultraviolet–solid-phase extraction–nuclear magnetic resonance, data and the 13C enrichment patterns of xanthyletin and seselin indicated that the pyran ring was formed by the methylerythritol phosphate pathway and that the coumarin moiety was derived from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Exposed to prenyltransferases, umbelliferone forms either osthenol, a precursor of 7,8-angular pyranocoumarins, or 7-demethylsuberosin-a precursor of linear pyranocoumarins [14]. In an experiment with carbon label conducted for orange seedlings (Citrus sinensis (L.) Osbeck) and rangpur seedlings (Citrus limonia Osbeck), it has been proven that the coumarin fragment of pyranocoumarins xanthyletin and seselin originate from the shikimate pathway (L-phenylalanine), and the pyran ring is formed via the methyl-erythrite-phosphate pathway [15]. Transformation and coupling of substitutes are most likely related to various transferases.…”
Section: Biosynthesis Of Pyranocoumarins In Cellsmentioning
confidence: 99%
“…Exposed to prenyltransferases, umbelliferone forms either osthenol, a precursor of 7,8-angular pyranocoumarins, or 7-demethylsuberosin-a precursor of linear pyranocoumarins [14]. In an experiment with carbon label conducted for orange seedlings (Citrus sinensis (L.) Osbeck) and rangpur seedlings (Citrus limonia Osbeck), it has been proven that the coumarin fragment of pyranocoumarins xanthyletin and seselin originate from the shikimate pathway (L-phenylalanine), and the pyran ring is formed via the methyl-erythrite-phosphate pathway [15]. Transformation and coupling of substitutes are most likely related to various transferases.…”
Section: Biosynthesis Of Pyranocoumarins In Cellsmentioning
confidence: 99%
“…Also, umbelliferone was exposed to a prenyl donor substrate (dimethylallyl pyrophosphate (DMAPP)) and transformed into demethylsuberosin or osthenol by prenyltransferase [ 47 , 48 ]. It was also shown that the biosynthesis of xanthyletin and seselin may be formed by a mevalonate-independent pathway from osthenol in Thamnosma montana [ 48 , 52 ]. Perhaps this stage is no less important for the formation of linear and angular pyranocoumarins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed on C. limonia identified coumarins (esculetin, xanthyletin, and seselin), a flavonoid (limonianin), and organic acids (tartaric, citric and ascorbic acids). [23][24][25][26] Esculetin was reported to possess anti-inflammatory, anti-oxidant, and antiproliferative activity against non-small-cell lung carcinoma (NSCLC). 25 Limonianin showed hepatoprotective effect on human hepatoma cells against D-galactosamine-induced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%